Innovative design method of the metamorphic hand. (25th January 2018) - Sun, Wei; Kong, Jianyi; Wang, Xingdong; Liu, Huaiguang
In order to solve the last centimeter problem of automated production, it is necessary to innovative design of flexible fixture. This article presents a metamorphic hand design method through the principle of metamorphic mechanism. Firstly, kinematic chain satisfying the requirements is obtained by number synthesis and structural synthesis. Then, the kinematic chain becomes a mechanism that meets the requirements using regeneration design rules. And the holographic matrix description method is used to describe the configuration transformation of the metamorphic mechanism. Furthermore, through the combination method of kinematic chain, the metamorphic clamp increases the two joint fingers into a metamorphic hand. Finally, the validity of the theoretical method is verified by physical experiments.